On the Reasonable Restriction in the Identification of Extortion Crime - Lu, Xize; Liu, Mengyuan (International Journal of Social Sciences and Public Administration, 2025)
As a compound crime violating both property rights and citizens' personal rights, has the problem of over-generalization in judicial practice, which adversely affects the protection of citizens' legitimate rights and interests and the stability of social order. Starting from the constituent elements of extortion, this paper analyzes the tendency of expansion in the current identification process and its causes by combining typical cases in judicial practice, and explores the necessity and specific paths for reasonably restricting the scope of identification of this crime. The study holds that the reasonable restriction in the identification of extortion should be realized by strictly defining the connotation and extension of "threats and coercion", clarifying the identification standards of "the purpose of illegal possession", and distinguishing the boundary between the exercise of legitimate rights and extortion. This is to balance the punitive and protective functions of criminal law and safeguard judicial justice.